Pulmonary Functions and Quality of Life in Osteoporotic and Osteopenic Subjects - Original Investigation - Özlem Solak; Fatma Fidan; İlknur Yiğit Gökçe; Ümit Seçil Demirdal; Gülderen Çalışkan; Vural Kavuncu; Mehmet Ünlü (Galenos Yayinevi, 2009)
Aim: Osteoporotic vertebral fractures and increased kyphotic angle may cause disturbances in pulmonary functions. Our aim was to evaluate pulmonary function and quality of life in osteoporotic patients. Material and Methods: Fifty-one patients with osteoporosis and 19 osteopenic subject, followed in our outpatient clinic, were included. Their demographics were recorded. All the subjects were submitted to pulmonary function test (PFT) and dorsal lateral radiography was obtained to measure Cobb angle. Global body pain was assessed using Visual Analogue Scale (VAS) and quality of life was assessed using Short Form-36 (SF-36) questionnaire. Results: The mean ages were 63.3±8.7 in osteoporosis and 55.3±7.3 in osteopenia groups (p=0.001). Body mass index of the osteoporosis group was significantly lower than osteopenia group (28.8±5.7 and 32.2±5.5, respectively, p=0.029). In osteoporosis group compared to osteopenia group, the absolute forced expiratory volume in 1 second (FEV1) (1.8±0.4 and 2.1±0.5, respectively, p=0.018) and absolute forced vital capacity (FVC) (2.2±0.5 and 2.6±0.6, respectively, p=0.005) were significantly lower. No differences were found between two groups concerning other PFT parameters. The mean Cobb angle was higher in osteoporosis group than osteopenia group, but the difference was not significant (32.7±12.4 and 28.5±9.5, respectively, p=0.194). When all the subjects were considered, no correlation was found between Cobb angle and PFT parameters (p>0.05). No significant difference was found between two groups in respect to VAS and SF-36 scores (p>0.05). Conclusion: We found absolute FEV1 and absolute FVC significantly lower in osteoporosis group compared to osteopenia group. But we observed no differences in % predicted FEV1 and % predicted FVC. We supposed that the differences were because the subjects in osteopenia group were younger and fatter. The pulmonary functions and quality of life of the osteoporotic patients with a kyphotic angle up to studied are not worse than the osteopenic people. (From the World of Osteoporosis 2009;15:11-5)